Analisis pengetahuan, sikap, dan tindakan dokter keluarga terhadap pemberian antibiotik di Sulawesi Utara - Ruswandi, Cyndhi Widya Sari; Palandeng, Henry Malcom Frank; Kuhon, Frelly Valentino (UNIVERSITAS SAM RATULANGI, 2025)
Background: Irrational antibiotic use remains a global health challenge and is a major driver of increasing antibiotic resistance. North Sulawesi showed an increase in the use of Access category antibiotics in 2021–2022, necessitating an evaluation to ensure clinical practices are in line with guidelines. Family doctors, as the frontline of primary health care, play a very important role in controlling the appropriate use of antibiotics. Aim: To determine the level of knowledge, attitudes, and actions of family doctors in prescribing antibiotics and to analyze the relationship between the length of practice of family doctors and their knowledge, attitudes, and actions. Methods: This study used a quantitative cross-sectional design through the distribution of a Google-form questionnaire to 91 family doctors working with BPJS in North Sulawesi. Univariate analysis was used to determine the frequency distribution of the research variables, while bivariate analysis used the Spearman Rank correlation test to assess the relationship between length of practice and knowledge, attitudes, and actions in prescribing antibiotics Results: The results showed that all respondents had good knowledge (100%) and attitudes (100%) regarding antibiotic administration, and most showed good practices (95.6%) while a small number showed adequate practices (4.4%). The correlation test results showed that there was no significant relationship between length of practice and knowledge (p = 0.556; r = -0.062), attitude (p = 0.714; r = -0.039), or actions (p = 0.801; r = -0.027). Conclusion: Family doctors in North Sulawesi have good knowledge, attitudes, and practices in prescribing antibiotics, and length of practice is not significantly related to these three variables.